D2D communication for spectral efficiency improvement and interference reduction: A survey - Abdullah H. Alquhali; Mardeni Roslee; Mohamad Y. Alias; Khalid S. Mohamed (Institute of Advanced Engineering and Science, 2020)
Device-to-device (D2D) communication system plays an extremely important role in fulfilling the demands of fourth generation (4G) and fifth generation (5G) technologies. 4G technology cannot meet high data demands. The D2D communication system is believed to provide major improvements in resource usage, energy efficiency, and overall throughput, which are the main demands for the 5G network. Some of the main issues in the D2D communication system involve spectrum efficiency and interference. Although many studies have been conducted on spectrum efficiency improvement and interference reduction, the issues still remain. A study should be conducted to obtain a better understanding of the D2D communication system and to develop a D2D scheme with efficient spectrum utilization and interference reduction. Many survey papers have been published on these issues, but the fundamental concepts behind the D2D communication system require investigation. In this study, we investigated and analyzed the fundamental concepts behind the D2D communication system to develop an efficient D2D resource allocation scheme with reduced interference.